KEANEKARAGAMAN MOLLUSCA SEBAGAI BIOINDIKATOR KUALITAS PERAIRAN DI KAWASAN TPA KEBON KONGOK LOMBOK BARAT - Athifah Athifah; Maya Nuansa Putri; Sahid Imam Wahyudi; Immy Suci Rohyani (Universitas Mataram, 2019)
Abstract: Research has been done in the area of Kebon Kongok landfill by looking at the diversity of Mollusca as a bioindicator of water quality. This research is important because the river in Kebon Kongok landfill area is utilized by the surrounding community for daily needs. The research was conducted in May-June 2018 at Sungai Ayu River, Gerung District, West Lombok which aims to provide information about the water quality in this area. The research was done by purposive sampling method using cruising technique. There are 3 research stations selected based on the difference of environmental conditions around the waters ofÃÂ Kebon Kongok landfill. Station 1 is located east of the Kebon Kongok landfill adjacent to the landfill waste pond landfill, station 2 is located in the northwest part of the Kebon Kongok landfill where it is located adjacent to the main river body and station 3 is located in the southwest adjacent to the residential area. There were 13 Mollusca species belonging to 8 families: Lymnaeidae, Ampullaroidae, Thiaridae, Viviparidae, Planorbidae, Ariophantidae, Neritidae and Corbiculidae. The Tarebia granifera of the Thiaridae family is the most common of 127, 92 and 47 in each station. There were Shannon-Wiener (H ') diversity index data where H' each station was 1.3, 1.5 and 1.4 respectively. This data concludes that the water quality around the Kebon Kongok landfill is moderately polluted with moderate diversity criteria (H '= 1.0-2.0).ÃÂ Key words: Kebon Kongok landfill, Indeks Shannon-Wienner, Mollusca, and Bioindicator.ÃÂ Abstrak: Telah dilakukan penelitian di kawasan TPA Kebon Kongok dengan melihat keanekaragaman Mollusca sebagai bioindikator kualitas perairan. Penelitian ini penting dilakukan mengingat sungai di kawasan TPA Kebon Kongok dimanfaatkan oleh masyarakat sekitar untuk kebutuhan sehari-hari. Penelitian telah dilakukan pada bulan Mei-Juni 2018 di sungai Taman Ayu Kecamatan Gerung,ÃÂ Lombok Barat yang bertujuan untuk memberikan informasi mengenai kualitas perairan di kawasan tersebut. Penelitian dilakukan dengan metode purposive sampling menggunakan teknik jelajah. Ada 3 stasiun penelitian yang dipilih berdasarkan perbedaan kondisi lingkungan di sekitar perairan TPA Kebon Kongok. Stasiun 1 terletak di sebelah timur TPA Kebon Kongok yang bersampingan dengan kolam limbah lindi TPA, stasiun 2 terdapat di bagian barat laut TPA Kebon Kongok dimana letaknya berdekatan dengan badan sungai utama dan stasiun 3 terletak di sebelah barat daya yang berdampingan dengan pemukiman penduduk. Ditemukan 13 spesies Mollusca yang tergabung dalam 8 famili yakniÃÂ Lymnaeidae, Ampullaroidae, Thiaridae, Viviparidae, Planorbidae, Ariophantidae, Neritidae dan Corbiculidae. Tarebia granifera dari famili Thiaridae merupakan individu terbanyak yakni 127, 92 dan 47 di masing-masing stasiun. Didapatkan data indeks keanekaragaman Shannon-Wiener (HÃ¢â¬â¢) dimana HÃ¢â¬â¢ setiap stasiun berturut-turut yakni 1.3, 1.5 dan 1.4. Data ini menyimpulkan bahwa kualitas perairan sekitar TPA Kebon Kongok adalah tercemar sedang dengan kriteria diversitas sedang (HÃ¢â¬â¢=1,0-2,0).ÃÂ Kata kunci: TPA Kebon Kongok, Indeks Shannon-Wienner, Mollusca, dan Bioindikator